Tinjauan Literatur Strategis Tentang Isu-Isu Kesehatan Masyarakat di Indonesia - A. Ainun Wulandari Nur; Rezky Putri Indarwati Abdullah; Ananda Hikmal Akbari (Rumah Sakit Ibnu Sina, Makassar, 2025)
Public health in Indonesia faces a dual burden of disease, persistent Stunting, service inequities, and emerging threats such as climate change, urbanization, and digital health transitions. A transparent literature synthesis is needed to identify critical issues, evidence gaps, and policy priorities. To map strategic public health issues in Indonesia and propose policy and research priorities based on thematic evidence synthesis. This study employed a scoping review of publications from 2019–2025 (with a focus on 2023–2025 while allowing foundational references for conceptual frameworks). Searches were conducted in academic databases and policy sources. Records were screened using predefined inclusion/exclusion criteria. Findings were synthesized thematically using an SDGs and social determinants of health lens. Evidence quality was categorized using a pragmatic appraisal by source type (peer-reviewed vs grey literature). A total of 32 sources were included (as listed in the reference list) and mapped into key themes: social determinants; environment and sanitation; nutrition/Stunting; communicable diseases and NCDs; health policy and systems; health behavior and education; maternal and child health; workforce and community cadres; and cross-cutting challenges (climate change–urbanization–digitalization). Key gaps include limited implementation/evaluation studies and inconsistent cross-region comparative evidence. The literature supports strengthening primary care, adopting evidence-informed policies grounded in social determinants, and prioritizing implementation research to evaluate community-based and system-level interventions.